Relationship between changes in microbiota induced by resveratrol and its anti-diabetic effect on type 2 diabetes - Fernandez-Quintela, Alfredo; Macarulla, María Teresa; Gómez-Zorita, Saioa; González, Marcela; Milton-Laskibar, Iñaki; Portillo, María P. (Frontiers in Nutrition, 2023)
Although a general healthy gut microbiota cannot be defined due to numerous internal and external individual factors, such as sex, age, ethnicity, genetics, environment, diet and drugs affect its composition, certain microbial species and gut microbiota compositions seem to be related to the progression of insulin resistance to type 2 diabetes, as well as the development of microvascular and macrovascular complications of diabetes. The present review aimed at gathering the reported information describing how resveratrol induced changes in microbiota composition can mediate the positive effects of this polyphenol on glucose homeostasis under type 2 diabetic conditions, both in animals and humans. Based on the fact that some changes observed in the gut microbiota of type 2 diabetic animals and patients are reversed by resveratrol treatment, and taking into account that some resveratrol mediated changes in gut microbiota composition are similar to those induced by anti-diabetic drugs such as metformin, it can be proposed that four genera, Alistipes, Allobaculum, Desulfovibrio and Blautia could be involved in the benefits of resveratrol on glycameic control. Nevertheless some limitations are observed in this research field: a) the number of studies analyzing both the effects of resveratrol on glucose homeostasis and microbiota composition in the same cohort of animals, in order to know the potential involvement of microbiota in the anti-diabetic effects of this phenolic compound, are very scarce and practically inexistent in the case of humans., b) the studies present inconsistencies concerning the effects of resveratrol on gut microbiota changes, c) the experimental design used do not allow the researchers to establish a causal relationship between the changes in microbiota and the anti-diabetic effect, in the vast majority of the studies, d) the knowledge about the role of each type of bacteria on glycaemic control is not sufficient so far.